Evaluación de la sábila “aloe vera barbadensis miller” como coadyuvante en la cicatrización de OSH (ooforo salpingo histerectomía) en caninas - Valdivieso Villagómez, Allison Sabrina (2021)
Aloe vera gel is a product of natural origin that has multiple beneficial properties such as anti-inflammatory, moisturizing, antioxidant, antiseptic, antipruritic and healing. The purpose of this research was to evaluate the healing effect of Aloe Vera on OSH (Ooforo Salpingo Hysterectomy) of canines and its economic value compared to a chemical product present on the market such as silver sulfadiazine spray. The research was carried out by implementing the experimental, descriptive, comparative and statistical method. 20 canines were used, divided into two treatments; TA (silver sulfadiazine) with one application of the product every 72 hours and TB (aloe vera gel) every 48 hours with a postoperative follow-up of nine days after surgery. The variables analyzed were the color of the wound, presence of exudate, edema, pain, pruritic reflex, contact dermatitis and edge dehiscence. The results did not show a significant difference (P> 0.05) in the largest number of parameters evaluated, except for the economic part of the application of the products, showing that aloe vera gel has a lower economic cost compared to silver sulfadiazine and which concludes that aloe vera gel helps in the healing, asepsis and de-inflammation of wounds produced by OSH in dogs, thus also being a product of easy acquisition and without a time limit of use.